2022
DOI: 10.1038/s41598-022-11487-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of summer hourly precipitation under different urbanization background in central China

Abstract: The relationship between sub-daily precipitation and urbanization is widely concerned because short-term precipitation is sensitive to urbanization and difficult to predict. Using the data of summer hourly precipitation and urban development during 2007–2019 at four urban stations and an atmospheric background monitoring station in central China, this study investigates the characteristics of hourly precipitation and hourly extreme precipitation (HEP) under different urbanization background. It is found that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Many studies have shown that when increases in urban heat island intensity (UHI) enhancement and aerosol concentration are superimposed with climate change, the impact of urbanization on extreme precipitation events is amplified (Seino et al, 2018;Zhang et al, 2018). Their frequency and intensity are aggravated Zhang et al, 2018;Huang et al, 2022;Tang et al, 2022), the probability of urban flood occurrence increases (Glisan et al, 2014;Zhang et al, 2018), and densely populated urban areas are more vulnerable to extreme weather conditions (Yu R. et al, 2018;Debbage and Shepherd, 2019;Zhang et al, 2019). Urbanization intensifies urban precipitation variability and enhances the occurrence of events such as typhoons or hurricanes, making the risk of urban floods several times higher than in suburban areas (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that when increases in urban heat island intensity (UHI) enhancement and aerosol concentration are superimposed with climate change, the impact of urbanization on extreme precipitation events is amplified (Seino et al, 2018;Zhang et al, 2018). Their frequency and intensity are aggravated Zhang et al, 2018;Huang et al, 2022;Tang et al, 2022), the probability of urban flood occurrence increases (Glisan et al, 2014;Zhang et al, 2018), and densely populated urban areas are more vulnerable to extreme weather conditions (Yu R. et al, 2018;Debbage and Shepherd, 2019;Zhang et al, 2019). Urbanization intensifies urban precipitation variability and enhances the occurrence of events such as typhoons or hurricanes, making the risk of urban floods several times higher than in suburban areas (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%